The Thermal and Mechanical Properties of Poly(ethylene-co-vinyl acetate) Random Copolymers (PEVA) and its Covalently Crosslinked Analogues (cPEVA) - Wang, Ke (Polymers (Basel), 2019)
The thermal and mechanical properties of poly(ethylene-co-vinyl acetate) random copolymers (PEVA) and its covalently crosslinked analogues (cPEVA) were controlled by the overall crystallinity of the polymer networks. The cPEVAs with different VA-content were synthesized by thermally-induced crosslinking of linear PEVA with dicumyl peroxide (DCP). This work was mainly concerned with the effect of vinyl acetate (VA) content on the crosslinking density, thermal and mechanical properties of PEVAs and cPEVAs, respectively. The chemical composition was analyzed by thermogravimetric analysis and (1)H-NMR. The thermal and mechanical properties of PEVAs and cPEVAs have been studied through a series of conventional analytical methods, including gel content determination, different scanning calorimetry, thermogravimetric analysis, dynamic mechanical thermal analysis and traditional mechanical measurements. The experimental results show that the thermal and mechanical properties of PEVAs and cPEVAs increase with decreasing the VA-content. A broad melting transition with a ΔT(m) in the range from 78 °C to 95 °C was observed for all polymer networks.